2021
DOI: 10.1002/cam4.4421
|View full text |Cite
|
Sign up to set email alerts
|

Cancer prevention, screening, and survivorship ECHO: A pilot experience with an educational telehealth program

Abstract: Introduction The American Cancer Society, Inc. (ACS) estimates that 37,940 Indiana residents were diagnosed with cancer in 2020, which remains the leading cause of death in the state. Across the cancer continuum, national goals have been established targeting recommended benchmarks for states in prevention, screening, treatment, and survivorship. Indiana consistently falls below most goals for each of these targeted categories. Methods To address these disparities, we implemented Project ECHO (Extension for Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…Our results support the ECHO model as an effective tool for strengthening the capacity of rural HCPs to deliver up‐to‐date, high‐quality cancer care to their patients 19 . Similar to an assessment of the Cancer Screening, Prevention, and Survivorship ECHO, 20 we found that the educational material delivered in ECHO sessions was relevant to HCP from diverse disciplines and that the online learning platform was advantageous during the COVID‐19 pandemic.…”
Section: Discussionsupporting
confidence: 73%
“…Our results support the ECHO model as an effective tool for strengthening the capacity of rural HCPs to deliver up‐to‐date, high‐quality cancer care to their patients 19 . Similar to an assessment of the Cancer Screening, Prevention, and Survivorship ECHO, 20 we found that the educational material delivered in ECHO sessions was relevant to HCP from diverse disciplines and that the online learning platform was advantageous during the COVID‐19 pandemic.…”
Section: Discussionsupporting
confidence: 73%
“…The PS participants were recruited from mailing lists of registrants for the Cancer ECHO program (since some registered but did not attend) and participants in IU PCP-targetted ECHO programs on other topics. Additionally, the program attracted learners from many disciplines other than PCPs, and they constituted an important part of the multidisciplinary dialogs in the program [ 22 ]. Considering this fact and our goal of maximizing study participation, we recruited both PCPs and non-PCPs from the PS group although we attempted to recruit as many PCPs as possible since they were the original target audience for the Cancer ECHO program.…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing the feedback from the surveys and focus groups from the pilot year, several key changes were made to the ECHO. 14 , 15 First, the second‐year curriculum of 24 planned ECHO sessions, including didactic sessions with relevant cases (see Table S1 ), was designed to be more accessible for learners from different educational backgrounds. A voluntary post‐session survey continued to be offered to gather feedback for real‐time quality improvement to adapt the curriculum.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline implementation infrastructure for the Cancer Prevention, Screening, and Survivorship ECHO was described in our pilot manuscript and retained for this second year of operation. 14 The hub team was recruited from pilot team members, each of whom serves as a specialist or expert in a wide range of oncology topics and geographically represents our catchment area (Indiana). Members Discussion: In this second year, this ECHO expanded to reach more participants with increased attendance and a more diverse distribution of roles within healthcare, which may be attributed to feedback-driven curriculum design.…”
Section: Implementation Of the Second Year Of Project Echomentioning
confidence: 99%